Antibiotic prophylaxis in cardiothoracic surgery in the United Kingdom: current practice. Issue 5 (May 1986) - Wilson, A P; Treasure, T; Sturridge, M F; Grüneberg, R N
Abstract : A survey was conducted of the current practice of antibiotic prophylaxis in cardiac surgery throughout the United Kingdom. Most surgeons (84%) use a regimen covering a broad spectrum of bacterial species that is continued for two to three days after the operation. The most used regimens are a combination of beta lactamase resistant penicillin with an aminoglycoside (44%) or a single broad spectrum cephalosporin (30%). Just 16% of surgeons preferred a narrow spectrum regimen effective against only the Gram positive organisms commonly responsible for postoperative infection in these patients. Antibiotic prophylaxis has been adopted by all cardiac surgeons in the United Kingdom but is sometimes continued longer than is indicated by the clinical or experimental evidence.